2017
DOI: 10.3892/etm.2017.5059
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cells repair the hippocampal neurons and increase the expression of IGF‑1 after cardiac arrest in rats

Abstract: The present study aimed to investigate the beneficial effects and underlying mechanisms of bone marrow mesenchymal stem cells (BMSCs) on global ischemic hypoxic brain injury. Cells collected from the femurs and tibias of male Sprague Dawley rats were used to generate BMSCs following three culture passages. A rate model of cardiac arrest (CA) was induced by asphyxia. One hour following return of spontaneous circulation (ROSC), BMSCs were transplanted through injection into the tail vein. Neurological status was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 40 publications
(41 reference statements)
2
15
0
Order By: Relevance
“…This early timing is consistent with a stroke model, in which rats receiving a hippocampal hNSC injection 24 h after middle cerebral artery occlusion (MCAO) showed an improvement in the foot-fault and adhesive removal tests administered 72 h later [32]. Stem cell therapy for global cerebral ischemia models involving 5-6 min of cardiac arrest, which leads to a mild brain injury, has been demonstrated beneficial at 3 days with adipose-derived stem cells [33] or bone marrow stem cells [34]. Intraventricular implantation of mesenchymal stem cells was reported to increase neurogenesis in the SVZ and the DG [35].…”
Section: Discussionsupporting
confidence: 66%
“…This early timing is consistent with a stroke model, in which rats receiving a hippocampal hNSC injection 24 h after middle cerebral artery occlusion (MCAO) showed an improvement in the foot-fault and adhesive removal tests administered 72 h later [32]. Stem cell therapy for global cerebral ischemia models involving 5-6 min of cardiac arrest, which leads to a mild brain injury, has been demonstrated beneficial at 3 days with adipose-derived stem cells [33] or bone marrow stem cells [34]. Intraventricular implantation of mesenchymal stem cells was reported to increase neurogenesis in the SVZ and the DG [35].…”
Section: Discussionsupporting
confidence: 66%
“…Compared with ischemic stroke, brain injury induced secondary to cardiac arrest has different conditions related to stem cell treatment (Table 2). 10,[16][17][18]51,[123][124][125][126][127] To date, BM-and AD-MSCs are the most commonly used stem cells in this pathology, and the cells are typically administered 1 to 2 hours after the return of spontaneous circulation. After 1 hour of brain ischemia, the subdural transplantation of iPSCs (1.0×10 6 ) is found to improve recovery in stroke rats.…”
Section: Optimal Dose Timing and Age Of Stem Cellsmentioning
confidence: 99%
“…Available preclinical studies indicate that IV doses ranging from 1×10 6 to 5×10 6 cells provide substantial behavioral gains in post-cardiac arrest rodents. 10,[16][17][18]51,[123][124][125] According to the allometric scaling approach from animals to humans recommended by the Food and Drug Administration, the equivalent MSC dose in humans is about 1.6×10 6 MSCs/kg. 9 The hMSC donor age is another critical factor affecting functional and structural outcomes in stroke affecting functional and structural outcomes in stroke.…”
Section: Optimal Dose Timing and Age Of Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, transplantation of bone marrow stromal cells (BMSCs) has emerged as a novel treatment for SCI (5)(6)(7). BMSCs are a population of heterogeneous mesenchymal cells located in the bone marrow that possess unlimited proliferative capacity and multidifferentiation properties (8,9). Furthermore, it has been reported that BMSCs have an important role in the immunomodulation of innate and adaptive immune processes in vitro and in vivo (10,11).…”
Section: Introductionmentioning
confidence: 99%